PENGARUH KARAKTERISTIK PEKERJAAN DAN DISIPLIN KERJA TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI KEPUASAN KERJA (Studi pada Rumah Sakit Umum Daerah Kabupaten Temanggung) (Students' Journal of Economic and Management, 2013)
Organizational commitment as a condition that is perceived by the employees who may cause a strong positive attitudes towards work organization owned, positive behavior was influenced among others by job satisfaction, job characteristics also work discipline. Furthermore, this study aimed to analyze the influence of job characteristics and work discipline of organizational commitment to the mediation of job satisfaction nurses in RSUD of Sub Province of Temanggung. Data collection using questionnaires, sampling using purposive sampling criteria respondents tenure of more than five years. Test instruments use validity and reliability, while the model test use R2 test (coefficient of determination), F test (Goodness of Fit) and t-test (t-test). Hypothesis Testing in this research use the regression analysis with t count criteria. Hypothesis testing is used t count frequency distribution test at significance level (α) of 5%. The results showed that no significant job characteristics on job satisfaction and organizational commitment, work discipline is significantly positive effect on job satisfaction but did not significantly affect organizational commitment, job satisfaction, while significant positive effect on organizational commitment and an intervening variable (mediation) which mediates work discipline organizational commitment. Based on the results of the research, Efforts to improve organizational commitment through work discipline can not avoid aspects of job satisfaction Keywords: Job Characteristics, Work Discipline, Job Satisfaction, Organisational Commitment